A study of job stress among professional accountants working in selected public accounting firms: A Malaysian case - Md. Ali, Azham (Universiti Utara Malaysia, 1992)
The study replicates and extends earlier studies on job stress in public accounting done in the US and UK. It is conducted through an extensive review of literature on job stress and field study using the same questionnaire as those used earlier in Gaertner and Ruhe (1981) and Lyall (1984). Slight modifications are made to the questionnaire to suit the Malaysian context. The study seeks answer to what may be the sources of stress, psychological outcomes and moderators of stressful situations in selected Malaysian public accounting firms and whether there exist significant linear relationships between the job stressors and mental strains. Furthermore, the study attempts to find out whether different firm sizes, functional areas and confronted and strains experienced by the professional accountants. The accountant respondents are drawn from a number of accounting firms located in urban centers in Peninsular Malaysia. The total number of completed responses to the questionnaire are 118, a response rate of 45 percent. The sample is largely composed of young, single, Chinese who have at least one university degree and presently working in small firms in the audit area. The findings of the study indicate that stressors faced by most respondents are quantitative workload, variations in workload, responsibility for persons and travel. Very few report confronting role conflict and role ambiguity. As for the mental strains, respondents do not show that they are experiencing any expect for job and workload dissatisfaction and pay inequity. Also, it is found that more than 70 percent of the respondents feel that they have job autonomy and that they do not possess the Type A personality traits. The existence of these moderators may be the reason why even though the respondents report relatively high level of a number of stressors at the same time they claim that they do not experience many of the mental strains. It seems also that there exists quite a number of significantly positive which range from very weak to moderate. Finally, the study shows that firm sizes and functional areas do not have any significant bearing on whether a professional accountant would be having different stressors and strains. The area which indicates the existence of many significant differences is the position levels. There are mostly available in the types of job stressors and not the types of mental strain experienced. This particular finding is similar to that found in Gaertner and Ruhe (1981). This study provides the implications that the accounting firms have got to be more on the watch out to the fact that many of their personnel are confronting a high level of stressors with no satisfaction found in their job, workload and salaries. Many report that they would not stay for long in the public accounting and would seek greener pastures elsewhere that have less job stress. Thus, it is recommended for the accounting finnstodo a number of things such as reassess the salaries paid to their personnel and include in the training programs information on how to cope successfully with stress which are unavoidable. This study has a number of limitations and further research is recommended with more adequately specified model and better methodology.